Biphase continuous spongy porous structure electrolyzed water composite diaphragm and preparation method thereof

By adopting a duplex continuous sponge-like porous structure electrolytic composite separator composed of alkali-resistant polymer and zirconium dioxide, the problems of high resistance and poor mechanical stability of the separator in the existing alkaline water electrolytic hydrogen production technology are solved, and efficient and stable hydrogen generation is achieved and maintenance costs are reduced.

CN119615275AActive Publication Date: 2025-03-14SUZHOU XIBEIYOU HYDROGEN ENERGY TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411542902.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-03-14
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

In the existing alkaline water electrolysis hydrogen production technology, the composite separator has a large resistance, poor mechanical stability, and insufficient maintenance cost and operating stability.

Method used

A biphasic continuous sponge-like porous structure electrolytic composite membrane consisting of alkali-resistant polymer and zirconium dioxide is adopted. The surface of the membrane has a porous layer and a biphasic continuous porous structure inside. A diaphragm is formed by a specific preparation method with a high porosity, uniform pore size, low resistance and good mechanical stability.

Benefits of technology

A composite separator with high chemical and mechanical stability, high porosity and small pore size in strong alkaline media is realized, which reduces the use and maintenance costs of alkaline water electrolytic cells and improves operating stability and electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615275A_ABST
    Figure CN119615275A_ABST
Patent Text Reader

Abstract

The invention discloses an electrolyzed water composite diaphragm which is composed of an alkali-resistant polymer and zirconium dioxide, the surface of the diaphragm is provided with a porous layer, and the interior of the diaphragm is provided with a biphase continuous porous structure. During preparation, an organic solvent and a diluent are mixed firstly, then the alkali-resistant polymer and nano zirconium dioxide particles are sequentially added to obtain a membrane casting solution; placing the membrane casting solution on a clean glass plate, and performing blade coating to prepare a liquid membrane; and finally, quickly putting into a coagulating bath, introducing an additive into the membrane casting solution, forming microscopic phase separation in advance by utilizing temperature, then carrying out solvent replacement, and enabling the liquid membrane to fall off from the glass plate to obtain the diaphragm. The invention has the performance characteristics of high porosity, uniform aperture, low resistance, good mechanical stability and long service life, is simple and reliable to prepare, and reduces the use and maintenance cost of the alkaline water electrolytic bath.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water electrolysis hydrogen production, and in particular to a dual-phase continuous sponge-like porous structure water electrolysis composite diaphragm and a preparation method thereof. Background Art

[0002] Fossil energy is a non-renewable energy source with decreasing reserves, while hydrogen energy, as a high-energy clean energy source, has the advantages of being recyclable, renewable, and clean. Therefore, the development of hydrogen energy is an effective way to reduce fossil energy consumption and promote the sustainable development of human society.

[0003] Hydrogen can be produced from a variety of sources, including fossil fuels, biomass, and water electrolysis. Among them, water electrolysis to produce hydrogen, as one of the technologies of renewable energy systems, provides a direct way to convert electrical energy into hydrogen energy. Currently, there are three types of electrolyzer systems used for hydrogen production: alkaline water electrolyzers, proton exchange membrane electrolyzers, and solid oxide electrolyzers. Among them, alkaline water electrolyzers are more commercialized than other water electrolysis methods due to their mature technology and lower costs. However, there are still some aspects of this technology that need to be improved, such as maintenance costs and operational stability.

[0004] The alkaline electrolyzer is mainly composed of three parts: the cell body, the electrode, and the diaphragm. The diaphragm plays a very important role in the alkaline electrolyzer. On the one hand, it must be able to prevent the mixing of hydrogen and oxygen to ensure the purity of hydrogen; on the other hand, it must allow the ions in the solution to pass through to ensure the normal electrolysis process, and the diaphragm should have as low resistance as possible to reduce the energy consumption of the electrolyzer.

[0005] In the early days of alkaline water electrolysis (AWE) research, asbestos was used as a diaphragm material for alkaline electrolyzers. However, its chemical properties are unstable under alkaline conditions, and toxic carcinogens are produced during the hydrogen production process, so it is banned internationally. Later, people discovered that polyphenylene sulfide (PPS) cloth is more effective as a diaphragm and is non-toxic, so PPS cloth replaced asbestos cloth as the second-generation diaphragm. With the continuous advancement of technology, a new generation of composite diaphragms with strong alkali resistance, high tensile strength, and excellent electrochemical properties have the advantages of both organic and inorganic diaphragms, making it a better choice for alkaline water electrolysis to produce hydrogen.

[0006] However, the surface of the general composite diaphragm is a dense layer, and the interior has a typical finger-like pore structure, which makes its resistance relatively large and its mechanical stability poor. Therefore, developing a composite diaphragm with high chemical and mechanical stability, high porosity and small pore size, and good gas barrier and wettability in a strong alkaline medium has become a technical problem that needs to be solved urgently in this technical field. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide a dual-phase continuous sponge-like porous structure water electrolysis composite diaphragm and a preparation method, which has the performance characteristics of high porosity, uniform pore size, low resistance, good mechanical stability and long service life. The preparation is simple and reliable, and the use and maintenance costs of alkaline water electrolyzers are reduced.

[0008] In order to solve the above technical problems, the present invention provides a composite membrane for electrolysis of water, which is composed of an alkali-resistant polymer and zirconium dioxide, has a porous layer on the surface of the membrane, and has a two-phase continuous porous structure inside, with a thickness of 100-500μm, a porosity of 30-80%, a pore size of 50-100nm, and a surface resistance of 0.030-0.100Ω·cm 2 , tensile strength is 2-7MPa.

[0009] Furthermore, the thickness of the diaphragm is 200-300um; the porosity is 50-70%; the pore size is 50-100nm; and the surface resistance is 0.040-0.070Ω·cm 2 ; The tensile strength is 3-5MPa. The smaller the thickness of the diaphragm, the greater the porosity, the smaller its surface resistance, but the mechanical strength and toughness decrease; the larger the thickness, the smaller the porosity, the better its mechanical strength and toughness, but the surface resistance increases. Therefore, the ultimate goal of the above condition parameters is to obtain a composite diaphragm with excellent comprehensive performance so that it does not have a short board effect.

[0010] A method for preparing a composite membrane for electrolysis of water comprises the following steps:

[0011] A: mixing an organic solvent and a diluent in proportion and stirring for 1-3 hours to prepare a first mixed solution, wherein the mass ratio of the organic solvent to the diluent is 1:1 to 1:5;

[0012] B: adding the alkali-resistant polymer to the first mixed solution and stirring for 24 hours to obtain a second mixed solution, wherein the mass proportion of the alkali-resistant polymer in the second mixed solution is 0.1-0.3;

[0013] C: adding nano zirconium dioxide particles to the second mixed solution prepared in step B and stirring for 4 to 6 hours, and obtaining a uniform milky white casting solution after degassing, wherein the mass ratio of zirconium dioxide to the alkali-resistant polymer is 0.5:1-3:1;

[0014] D: placing the casting solution prepared in step C on a clean glass plate, and using a scraper to scrape the casting solution to prepare a liquid film;

[0015] E: The liquid film prepared in step D is quickly placed into a coagulation bath. The polymer and diluent in the liquid film first undergo thermally induced phase separation (because heat transfer is much faster than mass transfer). Then the organic solvent and diluent in the liquid film are exchanged with water to form a two-phase continuous sponge-like porous structure. The liquid film falls off the glass plate to obtain a diaphragm.

[0016] Furthermore, the organic solvent in step A is one or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylacetamide and N,N-dimethylformamide, the diluent is one or more of diethylene glycol, polyethylene glycol 200, polyethylene glycol 300, polyethylene glycol 400, and the mass ratio of the organic solvent to the diluent is 1:1.7-1:2.5.

[0017] Furthermore, the alkali-resistant polymer in step B is one or more combinations of polysulfone, polyethersulfone, polyphenylsulfone, and polyphenylene sulfone, and the mass proportion of the alkali-resistant polymer is 0.15-0.2.

[0018] Furthermore, the mass ratio of zirconium dioxide to alkali-resistant polymer added in step C is 1:1-2:1.

[0019] Furthermore, in step D, the distance between the scraper and the glass plate is 100-750 um, preferably 200-500 um.

[0020] Furthermore, in step E, the coagulation bath temperature is 30-70° C., and the coagulation bath time is 1-10 min.

[0021] Beneficial effects of the present invention:

[0022] 1. The membrane-forming system is composed of an alkali-resistant polymer, an organic solvent and a diluent, and has a low critical solution temperature (LCST). Rapid thermally induced phase separation can be achieved by controlling the temperature of the coagulation bath, forming a porous layer on the surface of the membrane instead of a dense surface layer obtained by traditional solvent phase separation; the pore size is small, and a symmetrical two-phase continuous sponge-like porous structure is formed on the entire cross-section of the membrane, thereby forming a composite membrane with high chemical and mechanical stability, high porosity and small pore size, as well as good gas barrier properties and wettability in a strong alkaline medium.

[0023] 2. In the present invention, the film casting process is simple, the microporous structure of the diaphragm is adjustable and controllable and easy to produce and prepare, with low cost and high benefit.

[0024] 3. In the prepared composite diaphragm for alkaline water electrolysis, the pore structure can be regulated by the proportion of polymer and diluent content and the coagulation bath temperature, thereby forming a three-dimensional sponge-like porous structure, giving the diaphragm excellent electrochemical properties and physical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a flow chart of the preparation of the composite diaphragm of the present invention;

[0026] Figure 2 is a microscopic morphology of the composite diaphragm material prepared in Example 1 of the present invention;

[0027] Figure 3 is a microscopic morphology of the composite diaphragm material prepared in Example 2 of the present invention;

[0028] Figure 4 is a microscopic morphology of the composite diaphragm material prepared in Example 3 of the present invention;

[0029] Figure 5 is a microscopic morphology of the composite diaphragm material prepared in Example 4 of the present invention;

[0030] Figure 6 is a microscopic morphology of the composite diaphragm material prepared in Example 5 of the present invention;

[0031] Figure 7 is a microscopic morphology of the composite diaphragm material prepared in Example 6 of the present invention;

[0032] Figure 8 is a microscopic morphology of the composite diaphragm material prepared in Comparative Example 1 of the present invention;

[0033] Fig. 9 is a microscopic morphology of the composite diaphragm material prepared in Comparative Example 2 of the present invention;

[0034] Fig.10 is a microscopic morphology of the composite diaphragm material prepared in Comparative Example 3 of the present invention;

[0035] Fig.11 It is a microscopic morphology of the composite diaphragm material prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0036] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0037] An embodiment of a composite membrane for electrolysis of water proposed by the present invention is composed of an alkali-resistant polymer and zirconium dioxide. The membrane surface has a porous layer and the interior has a two-phase continuous porous structure, which can also be called a two-phase continuous three-dimensional sponge-like porous structure. The two-phase continuous porous structure can be understood as having channels extending from the first surface of the membrane toward the second surface and from the second surface of the membrane toward the first surface. There are also through holes in the pores in the lateral direction, thereby forming a three-dimensional sponge-like structure. The membrane thickness is 200-300um; the porosity is 50-70%; the pore size is 50-100nm; the surface resistance is 0.040-0.070Ω·cm 2 ; The tensile strength is 3-5MPa. The smaller the thickness of the diaphragm, the greater the porosity, the smaller its surface resistance, but the mechanical strength and toughness decrease; the larger the thickness, the smaller the porosity, the better its mechanical strength and toughness, but the surface resistance increases. Therefore, the ultimate goal of the above condition parameters is to obtain a composite diaphragm with excellent comprehensive performance, so that it does not have a short board effect, has high porosity, uniform pore size, low resistance, good mechanical stability and long service life, and further reduces the use and maintenance costs of alkaline water electrolyzers.

[0038] The present invention also proposes a method for preparing a composite diaphragm using a reverse thermally induced phase separation method, so as to form a two-phase (gas-solid) continuous three-dimensional sponge-like porous structure that is consistent inside and outside, as described in detail in the following case:

[0039] Example 1

[0040] Preparation of polyethersulfone composite diaphragm material for alkaline water electrolysis, refer to Figure 1 (1) Weigh 50g of N,N-dimethylacetamide (DMAc) solvent and place it in a beaker, then weigh 75g of PEG200 and add it to the beaker (ratio is 1:1.5), and mechanically stir for 2h to obtain a transparent and uniform premixed organic solution; (2) Weigh 22.06g of polyethersulfone (15%) and add it to the premixed organic solution, and mechanically stir for 24h to obtain a transparent and uniform polymer solution; (3) Weigh 22.06g of zirconium dioxide particles (1:1), and stir while The mixture was slowly added to the polymer solution in batches while stirring, mechanically stirred for 4 h and degassed to obtain a milky white uniform casting solution; (4) the casting solution was placed on a clean glass plate, the distance between the scraper and the glass plate was adjusted to 500 μm, and the scraper was slowly moved at a uniform speed to spread the casting solution on the glass plate to form a liquid film; (5) the liquid film was quickly placed in a 30°C deionized water bath for 5 min to allow phase separation and solvent exchange to occur, and a composite membrane was obtained, the surface and cross-sectional microstructures of which are shown in FIG. Figure 2 The performance test results are shown in Table 1.

[0041] Example 2

[0042] Preparation of polyethersulfone composite diaphragm material for alkaline water electrolysis. (1) Weigh 50g of N,N-dimethylacetamide (DMAc) solvent and place it in a beaker, then weigh 115g of PEG200 (1:2.3) and add it to the beaker. After mechanical stirring for 2h, a transparent and uniform premixed organic solution is obtained; (2) Weigh 29.12g of polyethersulfone (15%) and add it to the premixed organic solution. Mechanical stirring is carried out for 24h to obtain a transparent and uniform polymer solution; (3) Weigh 29.12g of zirconium dioxide particles (1:1), and stir at the same time. The mixture was slowly added to the polymer solution in batches while stirring, and a milky white uniform casting solution was obtained after mechanical stirring for 4 hours; (4) the casting solution was placed on a clean glass plate, the distance between the scraper and the glass plate was adjusted to 500 μm, and the scraper was slowly moved at a uniform speed to spread the casting solution on the glass plate to form a liquid film; (5) the liquid film was quickly placed in a 30°C deionized water bath for 5 minutes to allow phase separation and solvent exchange to occur, and a composite membrane was obtained, the surface and cross-sectional microstructures of which are shown in FIG. Figure 3 The performance test results are shown in Table 1.

[0043] Example 3

[0044] Preparation of polyethersulfone composite diaphragm material for alkaline water electrolysis. (1) Weigh 50g of N,N-dimethylacetamide (DMAc) solvent and place it in a beaker, then weigh 75g of PEG200 (1:1.5) and add it to the beaker, and mechanically stir for 2h to obtain a transparent and uniform premixed organic solution; (2) Weigh 25.6g of polyethersulfone (17%) and add it to the premixed organic solution, and mechanically stir for 24h to obtain a transparent and uniform polymer solution; (3) Weigh 25.6g of zirconium dioxide particles (1:1) and stir while (4) placing the above-mentioned casting liquid on a clean glass plate, adjusting the distance between the scraper and the glass plate to 500 μm, and slowly moving the scraper at a uniform speed to spread the casting liquid on the glass plate to form a liquid film; (5) quickly placing the above-mentioned liquid film in a water bath at 30°C deionized water for 5 minutes to cause phase separation and solvent exchange, and obtaining a composite membrane, the surface and cross-sectional microstructure of which are as follows: Figure 4 The performance test results are shown in Table 1.

[0045] Example 4

[0046] Preparation of polyethersulfone composite diaphragm material for alkaline water electrolysis. (1) Weigh 50g of N,N-dimethylacetamide (DMAc) solvent and place it in a beaker, then weigh 115g of PEG200 (1:2.3) and add it to the beaker, and mechanically stir for 2h to obtain a transparent and uniform premixed organic solution; (2) Weigh 33.8g of polyethersulfone (17%) and add it to the premixed organic solution, and mechanically stir for 24h to obtain a transparent and uniform polymer solution; (3) Weigh 33.8g of zirconium dioxide particles (1:1) and stir while The mixture was slowly added to the polymer solution in batches while stirring, and a milky white uniform casting liquid was obtained after mechanical stirring for 4 hours; (4) the casting liquid was placed on a clean glass plate, the distance between the scraper and the glass plate was adjusted to 500 μm, and the scraper was slowly moved at a uniform speed to spread the casting liquid on the glass plate to form a liquid film; (5) the liquid film was quickly placed in a 30°C deionized water bath for 5 minutes to cause phase separation and solvent exchange, and a composite membrane was obtained, the surface and cross-sectional microstructure of which are shown in FIG. Figure 5 The performance test results are shown in Table 1.

[0047] Example 5

[0048] Preparation of polyethersulfone composite diaphragm material for alkaline water electrolysis. (1) Weigh 50g of N,N-dimethylacetamide (DMAC) solvent and place it in a beaker, then weigh 115g of PEG200 (1:2.3) and add it to the beaker, and mechanically stir for 2h to obtain a transparent and uniform premixed organic solution; (2) Weigh 33.8g of polyethersulfone (17%) and add it to the premixed organic solution, and mechanically stir for 24h to obtain a transparent and uniform polymer solution; (3) Weigh 33.8g of zirconium dioxide particles (1:1) and stir while The mixture was slowly added to the polymer solution in batches while stirring, and a milky white uniform casting liquid was obtained after mechanical stirring for 4 hours; (4) the casting liquid was placed on a clean glass plate, the distance between the scraper and the glass plate was adjusted to 500 μm, and the scraper was slowly moved at a uniform speed to spread the casting liquid on the glass plate to form a liquid film; (5) the liquid film was quickly placed in a 50°C deionized water bath for 5 minutes to allow phase separation and solvent exchange to occur, and a composite membrane was obtained, the surface and cross-sectional microstructures of which are shown in FIG. Figure 6 The performance test results are shown in Table 1.

[0049] Example 6

[0050] Preparation of polyethersulfone composite diaphragm material for alkaline water electrolysis. (1) Weigh 50g of N,N-dimethylacetamide (DMAc) solvent and place it in a beaker, then weigh 115g of PEG200 (1:2.3) and add it to the beaker, and mechanically stir for 2h to obtain a transparent and uniform premixed organic solution; (2) Weigh 33.8g (17%) polyethersulfone and add it to the premixed organic solution, and mechanically stir for 24h to obtain a transparent and uniform polymer solution; (3) Weigh 33.8g of zirconium dioxide particles (1:1) and stir while The mixture was slowly added to the polymer solution in batches while stirring, and a milky white uniform casting liquid was obtained after mechanical stirring for 4 hours; (4) the casting liquid was placed on a clean glass plate, the distance between the scraper and the glass plate was adjusted to 500 μm, and the scraper was slowly moved at a uniform speed to spread the casting liquid on the glass plate to form a liquid film; (5) the liquid film was quickly placed in a 70°C deionized water bath for 5 minutes to cause phase separation and solvent exchange, and a composite membrane was obtained, the surface and cross-sectional microstructure of which are shown in FIG. Figure 7 The performance test results are shown in Table 1.

[0051] In the above-mentioned multiple embodiments, PEG200 is introduced into the casting solution as a non-solvent additive. As the amount of PEG200 increases, the interaction between polyethersulfone and the mixed solvent becomes weaker, and the temperature is used to form a pre-liquid phase PEG200 / polyethersulfone two-phase continuous structure, which lays the foundation for the final formation of a sponge-like porous structure. In addition, as the mass ratio of PEG200 / DMAc increases, the viscosity of the casting solution also increases, which in turn affects the solvent exchange rate between the casting solution and the coagulation bath, and finally achieves effective control of the microporous structure of the diaphragm.

[0052] In addition, comparative experiments were conducted using other diluents, namely PEG300 and PEG400, as additives. The membranes were prepared under the conditions of organic solvent (NMP): diluent = 1:2.3, 17% solid content of alkali-resistant polymer (PES), 50°C coagulation bath (deionized water), and 500μm scraper gap (see Example 5). Compared with the diaphragm prepared with PEG200, the overall performance was slightly reduced.

[0053] Comparative Example 1

[0054] The difference from the embodiment is that PEG200 is not added to prepare the polyethersulfone composite diaphragm material for alkaline water electrolysis. (1) Weigh 100g of N,N-dimethylacetamide (DMAc) solvent and place it in a beaker, then weigh 20.48g (17%) of polyethersulfone and add it to the organic solution, mechanically stir for 24h to obtain a transparent and uniform polymer solution; (2) Weigh 20.48g of zirconium dioxide particles (1:1), slowly add it to the polymer solution in batches while stirring, and mechanically stir for 4h to obtain a milky white uniform casting liquid; (3) Place the above casting liquid on a clean glass plate, adjust the distance between the scraper and the glass plate to 500μm, and slowly move the scraper at a uniform speed to spread the casting liquid on the glass plate to form a liquid film; (4) Quickly place the above liquid film in a 30℃ deionized water water bath for 5min, phase separation and solvent exchange occur, and a composite diaphragm is obtained, and its surface and cross-sectional micromorphology are as follows: Figure 8 The performance test results are shown in Table 1.

[0055] Comparative Example 2

[0056] Different from the embodiment, polysulfone (PSU) is used as an alkali-resistant polymer to prepare a polysulfone composite diaphragm material for alkaline water electrolysis. (1) Weigh 50g of N,N-dimethylacetamide (DMAc) solvent and place it in a beaker, then weigh 115g of PEG200 (1:2.3) and add it to the beaker, and mechanically stir for 2h to obtain a transparent and uniform premixed organic solution; (2) Weigh 33.8g (17%) polysulfone and add it to the premixed organic solution, and mechanically stir for 24h to obtain a transparent and uniform polymer solution; (3) Weigh 33.8g of zirconium dioxide particles (1:1), and stir while The mixture was slowly added to the polymer solution in batches while stirring, and a milky white uniform casting liquid was obtained after mechanical stirring for 4 hours; (4) the casting liquid was placed on a clean glass plate, the distance between the scraper and the glass plate was adjusted to 500 μm, and the scraper was slowly moved at a uniform speed to spread the casting liquid on the glass plate to form a liquid film; (5) the liquid film was quickly placed in a 70°C deionized water bath for 5 minutes to cause phase separation and solvent exchange, and a composite membrane was obtained, the surface and cross-sectional microstructure of which are shown in FIG. Fig. 9 The performance test results are shown in Table 1.

[0057] Comparative Example 3

[0058] The difference from the embodiment is that N,N-dimethylformamide (DMF) is used as an organic solvent to prepare a polyethersulfone composite diaphragm material for alkaline water electrolysis. (1) Weigh 50g of N,N-dimethylformamide (DMF) solvent and place it in a beaker, then weigh 115g of PEG200 (1:2.3) and add it to the beaker, and mechanically stir for 2h to obtain a transparent and uniform premixed organic solution; (2) Weigh 33.8g (17%) polyethersulfone and add it to the premixed organic solution, and mechanically stir for 24h to obtain a transparent and uniform polymer solution; (3) Weigh 33.8g of zirconium dioxide particles (1:1), and stir while The mixture was slowly added to the polymer solution in batches while stirring, and a milky white uniform casting liquid was obtained after mechanical stirring for 4 hours; (4) the casting liquid was placed on a clean glass plate, the distance between the scraper and the glass plate was adjusted to 500 μm, and the scraper was slowly moved at a uniform speed to spread the casting liquid on the glass plate to form a liquid film; (5) the liquid film was quickly placed in a 30°C deionized water bath for 5 minutes to cause phase separation and solvent exchange, and a composite membrane was obtained, the surface and cross-sectional microstructure of which are shown in FIG. Fig.10 The performance test results are shown in Table 1.

[0059] Comparative Example 4

[0060] What is different from the embodiment is that N-methylpyrrolidone (NMP) is used as the organic solvent and polysulfone (PSU) is used as the alkali-resistant polymer to prepare the traditional polysulfone composite diaphragm material for alkaline water electrolysis. (1) Weigh 100 g of N-methylpyrrolidone (NMP) solvent and place it in a beaker for stirring. Then weigh 18 g of polysulfone polymer and slowly add it to the organic solvent in batches while stirring. After mechanical stirring for 4 hours, a transparent and uniform polysulfone solution is obtained; (2) Weigh 54 g of zirconium dioxide particles and slowly add it to the polymer solution in batches while stirring. After mechanical stirring for 4 hours, a milky white and uniform casting liquid is obtained; (3) The casting liquid is placed on a clean glass plate, the distance between the scraper and the glass plate is adjusted to 500 μm, and the scraper is slowly moved at a uniform speed to spread the casting liquid on the glass plate to form a liquid film; (4) The liquid film is quickly placed in a 30°C deionized water bath for 5 minutes to cause phase separation and solvent exchange, and a composite diaphragm is obtained, and its surface and cross-sectional micromorphology are as follows: Fig.11 The performance test results are shown in Table 1.

[0061] It can be seen from the accompanying drawings that the surfaces of Examples 1-3 present a dense layer, while the cross sections are all finger-like pore structures, while the surfaces and cross sections of Examples 4-6 present a three-dimensional network-like pore structure. This is because as the ratio of organic solvent to diluent increases, a more stable and uniform two-phase continuous structure is formed in the liquid phase, so that it is easier to form a three-dimensional network when phase separation occurs. By comparing Example 2 with Example 4, it can be found that even if the ratio of organic solvent to diluent is the same, the different polymer solid content also leads to the formation of different pore structures. This is because as the polymer solid content increases, the viscosity of the casting liquid increases and the increase is high. When phase separation occurs, the solvent replacement resistance increases, the rate decreases, and finger-like pores are not formed. By comparing the data in Table 1, it is found that although Examples 1-3 have a finger-like pore structure that is easier to transmit, they have higher surface resistance and bubble point, which is the result of the influence of the density of their surface layer; on the other hand, by comparing Examples 4-6, it can be found that as the coagulation bath temperature increases, the pore structure becomes looser, so the surface resistance and bubble point also decrease. The final preferred embodiment is 4-6.

[0062] Table 1 shows the preparation conditions and performance test results of the diaphragms in Examples 1-6 and Comparative Examples 1-4.

[0063]

[0064]

[0065] The above embodiments are only preferred embodiments for fully illustrating the present invention, and the protection scope of the present invention is not limited thereto. Any equivalent substitution or change made by a person skilled in the art based on the present invention is within the protection scope of the present invention.

Claims

1. A composite membrane for electrolysis of water, characterized in that: It is composed of alkali-resistant polymer and zirconium dioxide. The membrane surface has a porous layer and the inside of the membrane has a two-phase continuous porous structure. The membrane has a thickness of 100-500μm, a porosity of 30-80%, a pore size of 50-100nm and a surface resistance of 0.030-0.100Ω·cm 2 .

2. The water electrolysis composite diaphragm according to claim 1, characterized in that: The thickness of the diaphragm is 200-300um; the porosity is 50-70%; the pore size is 50-100nm; and the surface resistance is 0.040-0.070Ω·cm 2 .

3. A method for preparing a composite membrane for electrolysis of water, characterized in that: The following steps are involved: A: mixing an organic solvent and a diluent in proportion and stirring for 1-3 hours to prepare a first mixed solution, wherein the mass ratio of the organic solvent to the diluent is 1:1 to 1:5; B: adding the alkali-resistant polymer to the first mixed solution and stirring for 24 hours to obtain a second mixed solution, wherein the mass proportion of the alkali-resistant polymer in the second mixed solution is 0.1-0.3; C: adding nano zirconium dioxide particles to the second mixed solution prepared in step B and stirring for 4 to 6 hours, and obtaining a uniform milky white casting solution after degassing, wherein the mass ratio of zirconium dioxide to the alkali-resistant polymer is 0.5:1-3:1; D: placing the casting solution prepared in step C on a clean glass plate, and using a scraper to scrape the casting solution to prepare a liquid film; E: The liquid film prepared in step D is quickly placed in a coagulation bath. The polymer and diluent in the liquid film first undergo thermally induced phase separation. Then the organic solvent and diluent in the liquid film are exchanged with water. The liquid film falls off the glass plate to obtain a diaphragm.

4. The method for preparing the composite membrane for water electrolysis according to claim 3, characterized in that: The organic solvent in step A is one or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylacetamide and N,N-dimethylformamide, the diluent is one or more of diethylene glycol, polyethylene glycol 200, polyethylene glycol 300 and polyethylene glycol 400, and the mass ratio of the organic solvent to the diluent is 1:1.7-1:2.

5.

5. According to the method for preparing a composite membrane for electrolysis of water as claimed in claim 3, the alkali-resistant polymer in step B is one or more combinations of polysulfone, polyethersulfone, polyphenylsulfone, and polyphenylene sulfone, and the mass proportion of the alkali-resistant polymer is 0.15-0.

2.

6. According to the method for preparing a composite membrane for electrolysis of water as claimed in claim 3, the mass ratio of zirconium dioxide to alkali-resistant polymer added in step C is 1:1-2:

1.

7. According to the method for preparing the composite membrane for electrolysis of water according to claim 3, in step D, the distance between the scraper and the glass plate is 100-750 um, preferably 200-500 um.

8. The method for preparing a composite membrane for electrolysis of water according to claim 3, wherein the coagulation bath temperature in step E is 30-70°C and the coagulation bath time is 1-10 min.

Citation Information

Patent Citations

  • High-hydrophilicity alkaline electrolyzed water diaphragm and preparation method thereof

    CN116334690A

  • Super-hydrophilic alkaline water electrolyser composite diaphragm and preparation method thereof

    CN117248240A

  • Composite diaphragm with super-hydrophilic surface and integral cross-linked structure for hydrogen production by alkaline water electrolysis and preparation method of composite diaphragm

    CN117512693A

  • Method for preparing alkaline electrolytic water hydrogen production diaphragm through composite thermally induced phase separation

    CN117758308A

  • Preparation method of diaphragm, diaphragm and alkaline electrolysis device

    CN118007185A